2013
DOI: 10.1002/hed.23470
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of a head and neck oncologic surgeon: The case mix index

Abstract: Head and neck oncologic surgeons increase the CMI for hospitals and ultimately influence the hospital's reimbursement. There is a need for increased collaboration between hospitals and departments in fostering and furthering their head and neck surgical oncology programs by taking CMI into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It is well known that inpatient otolaryngology cases have a high CMI, primarily due to the complexity of head and neck oncology patients and high complexity values assigned to tracheostomy patients. 5 Intuitively, otolaryngology patients with a high CMI also have high rates of 30-day readmission rates and high rates of postoperative complications, all of which increase total costs. [19][20][21][22][23][24] Patients with high CMI may also have increased costs inherent to their disease process, regardless of interventions performed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well known that inpatient otolaryngology cases have a high CMI, primarily due to the complexity of head and neck oncology patients and high complexity values assigned to tracheostomy patients. 5 Intuitively, otolaryngology patients with a high CMI also have high rates of 30-day readmission rates and high rates of postoperative complications, all of which increase total costs. [19][20][21][22][23][24] Patients with high CMI may also have increased costs inherent to their disease process, regardless of interventions performed.…”
Section: Discussionmentioning
confidence: 99%
“…CMI has been shown to explain variations in cost between hospitals, with high CMI correlating with increasing cost. 5-7 Similarly, patient volume has been established to negatively affect mortality outcomes in general surgical patients. 8…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…24 Multidisciplinary expertise in high-volume centers can affect outcome, given that TL, PL, and CRT can be operator-dependent and influenced by surgeon and radiation oncologist experience. 25,26 We found that 11.6% of patients were treated at a community facility, 44.8% were treated at a comprehensive community facility, and 43.6% were treated at an academic facility. Surgical expertise and high-quality RT design and delivery (including target-volume delineation and the use of an intensity-modulated RT technique) affect outcomes, and we attempted to mitigate their confounding effects in this analysis by adjusting for treatment facility type in our multivariate analyses.…”
Section: Discussionmentioning
confidence: 88%